Concurrent tobacco and khat use is associated with blunted cardiovascular stress response and enhanced negative mood: a cross‐sectional investigation. (7th April 2014) - al'Absi, Mustafa; Nakajima, Motohiro; Dokam, Anisa; Sameai, Abed; Alsoofi, Mohamed; Saem Khalil, Najat; Al Habori, Molham
<x xml:space="preserve">Abstract</x> Objectives Khat (Catha edulis), an amphetamine‐like plant, is widely used in East Africa and the Arabian Peninsula and is becoming a growing problem in other parts of the world. The concurrent use of tobacco and khat is highly prevalent and represents a public health challenge. We examined for the first time associations of the concurrent use of tobacco and khat with psychophysiological responses to acute stress in two sites in Yemen. Methods Participants (N = 308; 135 women) included three groups: users of khat and tobacco, users of khat alone, and a control group (nonsmokers/nonusers of khat). These individuals completed a laboratory session in which blood pressures (BP), heart rate, and mood measures were assessed during rest and in response to acute stress. Results Concurrent use of khat and tobacco was associated with attenuated systolic BP, diastolic BP, and heart rate responses to laboratory stress (ps < 0.05) and with increased negative affect relative to the control group (ps < 0.05). Conclusions Results demonstrated blunted cardiovascular responses to stress and enhanced negative affect in concurrent khat and tobacco users. These findings extend previous studies with other substances and suggest that adverse effects of khat use may lie in its association with the use of tobacco. Copyright © 2014 John Wiley & Sons, Ltd.